Lamas, shamans and ancestors : village religion in Sikkim. - Balikci, Anna (Brill's Tibetan studies library ;, 2008)
This careful study of the co-existence over time of Buddhism and shamanism among the Lhopo (Bhutia) people of Sikkim sheds new light on their supposedly hostile relationship. It examines the working relationships between Buddhist lamas and practitioners of bon, taking into consideration the sacred history of the land as well as its more recent political and economic transformation. Their interactions are presented in terms of the contexts in which lamas and shamans meet, these being rituals of the sacred land, of the individual and household, and of village and state. Village lamas and shamans are shown to share a conceptual view of reality which is at the base of their amiable coexistence. In contrast to the hostility which, the recent literature suggests, characterizes the lama-shaman relationship, their association reveals that the real confrontation occurs when village Buddhism is challenged by its conventional counterpart -- Présentation de l'éditeur.